Teaching and research in Malaysian public universities: Synergistic or antagonistic? - Norzaini Azman (Springer Netherlands, 2014)
The Malaysian higher education system has undergone many reforms in the last two decades. These reforms have had radical implications for all aspects of the professional lives of university academics, particularly in their teaching and research as well as in their relations with institutional governance, infrastructure and facilities and remuneration. This chapter briefly discusses the consequences of the changing university system and institutional environments for teaching and research in the Malaysian public universities. It then examines a set of available data from the 2007 CAP study to investigate how academics use their time for teaching and research and how they perceive the teaching and research nexus. This chapter explores aspects of teaching and research using several determinants—perception of teaching and research environment, workload and preference, teaching and research processes, perception of a nexus—and compares them by university type. Several implications particularly in relation to the institutional policies and practices are offered to provide support for the coexistence of research and teaching in the Malaysian public universities.